Drosophila Cellular Immunity Against Parasitoid Wasps: A Complex and Time-Dependent Process - Kim-Jo, Chami; Gatti, Jean-Luc; Poirié, Marylène (Frontiers in Physiology, 2019)
Host-parasitoid interactions are among the most studied interactions between invertebrates because of their fundamental interest – the evolution of original traits in parasitoids - and applied, parasitoids being widely used in biological control. Immunity and in particular cellular immunity is central in these interactions, the host encapsulation response being specific for large foreign bodies such as parasitoid eggs. Although already well-studied in this species, recent data on Drosophila melanogaster have unquestionably improved knowledge of invertebrate cellular immunity. At the same time, the venomics of parasitoids has expanded, notably those of Drosophila. Here, we summarize and discuss these advances, with a focus on an emerging "time-dependent" view of interactions outcome at the intra- and interspecific level. We also present issues still in debate and prospects for study. Data on the Drosophila-parasitoid model paves the way to new concepts in insect immunity as well as parasitoid wasp strategies to overcome it.